The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1159/000495232
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts Accelerate Malignant Progression of Non-Small Cell Lung Cancer via Connexin 43-Formed Unidirectional Gap Junctional Intercellular Communication

Abstract: Background/Aims: Gap junctions, which are assembled by connexins, can directly connect the cytoplasm of adjacent cells and enable gap junctional intercellular communication (GJIC) as well as metabolic coupling between neighboring cells. Here, we investigated the role of connexin 43 (Cx43) and its derived GJIC in the interplay between non-small cell lung cancer (NSCLC) cells and cancer-associated fibroblasts (CAFs). Methods: CAFs and NSCLC cells were co-cultured with direct contact and separated using flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…Moreover, mRNA expression is typically derived from all cells present in the tumour sample (e.g., in the lung, there would be a mix of pneumocytes, bronchial epithelium, endothelial cells, macrophages and other cell types). Indeed, a recent study showed that cancer-associated fibroblasts can form Cx43-mediated gap junctions with NSCLC cells to support their malignant progression [64]. The ratios of these cell types in a tumour change.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mRNA expression is typically derived from all cells present in the tumour sample (e.g., in the lung, there would be a mix of pneumocytes, bronchial epithelium, endothelial cells, macrophages and other cell types). Indeed, a recent study showed that cancer-associated fibroblasts can form Cx43-mediated gap junctions with NSCLC cells to support their malignant progression [64]. The ratios of these cell types in a tumour change.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that CAFs are able to stimulate cancer cell proliferation and progression through multiple mechanisms. For instance, in a lung cancer model, CAFs underwent increased aerobic glycolysis and promoted the epithelial mesenchymal transition, migration and invasion of non-small-cell lung carcinoma (NSCLC) cells, in contrast, NSCLC cells experienced enhanced oxidative phosphorylation upon CAF stimulation, with an increase in ATP generation, thereby an activation of the PIK3/Akt and MAPK/ERK pathways occurred (123). Furthermore, colorectal cancer cells induce oxidative stress in microenvironment fibroblast, which then undergo metabolic changes, including increased expression of glycolytic enzymes, reduced TCA cycle enzymes and autophagy proteins such as microtubule-associated protein 1A/1B-light chain 3 (LC3), Bcl-2 interacting protein 3(BNIP3), and p62 (124).…”
Section: Lactate Exchange Between Cancer Cells and Cafs: Reverse Warbmentioning
confidence: 99%
“…The abnormal expression of PKM promoted cancer growth, invasion, and metastasis by governing aerobic glycolysis (Prakasam et al, 2017;Zahra et al, 2020) and induced cancer treatment resistance (Calabretta et al, 2016). Furthermore, PKM is overexpressed in non-small cell lung cancer (NSCLC) and involved in the development and prognosis of NSCLC (Luo et al, 2018). TPI1 is a crucial enzyme in carbohydrate metabolism, catalyzing the interconversion of dihydroxyacetone phosphate and d-glyceraldehyde-3-phosphate during glycolysis and gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%